JCGG 2018
DOI: 10.24816/jcgg.2018.v9i1.06
|View full text |Cite
|
Sign up to set email alerts
|

Frailty and its relationship with mortality among older adults from a Brazilian community: A cohort study

Abstract: Background/Purpose: People are living longer. However, the aging process, coupled with lifestyle and health conditions, may lead to what is known as frailty syndrome. There is a consensus among researchers in the field that frailty is associated with adverse health outcomes, such as functional decline, dependency, recurrent falls, fractures, institutionalization, hospitalization and death. The aim of the present study was to analyze the relationship between frailty and mortality in a population of older people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 8 publications
1
14
2
Order By: Relevance
“…Thus, the elderly who seek medical and hospital care frequently may have a more significant functional impairment, which generates disabilities and risk of adverse outcomes. Considering the fragility issue, studies (29,40) evidenced the association between this factor and mortality, which did not appear in this study. A Brazilian study conducted with community-dwelling elderly individuals in a 66-month follow-up identified that frailty increased during the follow-up period and was associated with mortality (29) .…”
Section: Discussioncontrasting
confidence: 69%
See 4 more Smart Citations
“…Thus, the elderly who seek medical and hospital care frequently may have a more significant functional impairment, which generates disabilities and risk of adverse outcomes. Considering the fragility issue, studies (29,40) evidenced the association between this factor and mortality, which did not appear in this study. A Brazilian study conducted with community-dwelling elderly individuals in a 66-month follow-up identified that frailty increased during the follow-up period and was associated with mortality (29) .…”
Section: Discussioncontrasting
confidence: 69%
“…The variable "inability to read" was also associated with mortality. Studies investigated the variable "education" (27,29) and found no association with mortality. However, the SABE study found out that the higher the survival of the elderly, the higher the level of education (31) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations